Conversion disorder with psychogenic vomiting and coexisting organic etiology in an adolescent: A case report - Ahmed, Tanbir; Syed, Sifat E; Anowar, Afsana Benta; Jahan, Syeda Rawnak; Morshed, Nahid Mahjabin (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Not applicable